Adipokines, diabetes and atherosclerosis: an inflammatory association - Freitas Lima, Leandro C.; Braga, Valdir de Andrade; do Socorro de França Silva, Maria; Cruz, Josiane de Campos; Sousa Santos, Sérgio H.; de Oliveira Monteiro, Matheus M.; Balarini, Camille de Moura (Frontiers in Physiology, 2015)
Cardiovascular diseases can be considered the most important cause of death in diabetic population and diabetes can in turn increase the risk of cardiovascular events. Inflammation process is currently recognized as responsible for the development and maintenance of diverse chronic diseases, including diabetes and atherosclerosis. Considering that adipose tissue is an important source of adipokines, which may present anti and proinflammatory effects, the aim of this review is to explore the role of the main adipokines in the pathophysiology of diabetes and atherosclerosis, highlighting the therapeutic options that could arise from the manipulation of these signaling pathways both in humans and in translational models.